Peran Jurnalisme Warga Dalam Mempromosikan Potensi Desa Bojong Kecamatan Bungbulang Kabupaten Garut - Fanaqi, Chotijah; Nuralam, Wanda Insan; Azriel, Maharaya (Universitas Garut, 2024)
Abstract The ease of internet access for the public has not been accompanied by the ability to use it constructively. Citizen journalism programs can be a means of using the internet, especially through social media, to encourage village potential. The existence of the Internet has stimulated renewed interest in the practice of citizen journalism. This service activity provides material and practice of citizen journalism in Bojong Village, Bungbulang District, Garut Regency which utilizes blogs and social media to promote village potential. The aim of this service is to present a model for using social media as a citizen journalism practice to promote village potential. The service method uses several approaches including lectures, questions and answers, discussions, and writing practice. The results of the service show that the citizen journalism program is in line with efforts to promote village potential, especially in the fields of culture, arts and the environment. Citizen journalists use the term